2017
DOI: 10.1111/eva.12569
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for planning genomic assessment and monitoring of locally adaptive variation to inform species conservation

Abstract: Identifying and monitoring locally adaptive genetic variation can have direct utility for conserving species at risk, especially when management may include actions such as translocations for restoration, genetic rescue, or assisted gene flow. However, genomic studies of local adaptation require careful planning to be successful, and in some cases may not be a worthwhile use of resources. Here, we offer an adaptive management framework to help conservation biologists and managers decide when genomics is likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
189
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(207 citation statements)
references
References 202 publications
2
189
0
4
Order By: Relevance
“…In particular, participants considered how and why detection rates differed between univariate and multivariate GEAs, exploring the use of latent factor mixed models (Frichot, Schoville, Bouchard, & Francois, 2013) and redundancy analysis (Forester, Jones, Joost, Landguth, & Lasky, 2016; Lasky et al., 2012), respectively. Recent work has shown that RDA is an effective means of detecting adaptive processes that result in weak, multilocus molecular signatures (Forester et al., 2018), providing a powerful tool for investigating the genetic basis of local adaptation and informing management actions to conserve evolutionary potential (Flanagan et al., 2017; Harrisson et al., 2014; Hoffmann et al., 2015). Finally, participants were encouraged to move beyond simply documenting candidate adaptive loci in their datasets, and instead focus on the ecological, evolutionary, and management‐relevant questions that can be addressed by more fully integrating a landscape genomic analytical framework.…”
Section: Improving Downstream Computational Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, participants considered how and why detection rates differed between univariate and multivariate GEAs, exploring the use of latent factor mixed models (Frichot, Schoville, Bouchard, & Francois, 2013) and redundancy analysis (Forester, Jones, Joost, Landguth, & Lasky, 2016; Lasky et al., 2012), respectively. Recent work has shown that RDA is an effective means of detecting adaptive processes that result in weak, multilocus molecular signatures (Forester et al., 2018), providing a powerful tool for investigating the genetic basis of local adaptation and informing management actions to conserve evolutionary potential (Flanagan et al., 2017; Harrisson et al., 2014; Hoffmann et al., 2015). Finally, participants were encouraged to move beyond simply documenting candidate adaptive loci in their datasets, and instead focus on the ecological, evolutionary, and management‐relevant questions that can be addressed by more fully integrating a landscape genomic analytical framework.…”
Section: Improving Downstream Computational Analysesmentioning
confidence: 99%
“…Technological and analytical advances now allow us to use many thousands of loci, gene expression, or epigenetics to address basic questions of relevance for conservation, such as identifying loci associated with local adaptation or adaptive potential in species face changing environments (Bernatchez, 2016; Flanagan, Forester, Latch, Aitken, & Hoban, 2017; Harrisson et al., 2014; Hoban et al., 2016; Hoffmann et al., 2015; Jensen, Foll, & Bernatchez, 2016; Le Luyer et al., 2017; Wade et al., 2016). As conservation genomics matures, new challenges are arising.…”
Section: Introductionmentioning
confidence: 99%
“…Is it simply an academic exercise to explore the genetic underpinnings of adaptive traits, or can this information have practical relevance for conservation? While debate surrounds the precise role of genomics in conservation (Garner et al, ; Kardos & Shafer, ; McMahon, Teeling, & Hoglund, ; Shafer et al, ), understanding adaptive variation and predicting evolutionary responses to environmental change is a fundamental goal shared between evolutionary and conservation biology (Flanagan, Forester, Latch, Aitken, & Hoban, ).…”
Section: Conservation Implications Of Genome‐to‐phenome‐to‐fitness Mapsmentioning
confidence: 99%
“…Is it simply an academic exercise to explore the genetic underpinnings of adaptive traits, or can this information have practical relevance for conservation? While debate surrounds the precise role of genomics in conservation Kardos & Shafer, 2018;McMahon, Teeling, & Hoglund, 2014;Shafer et al, 2015), understanding adaptive variation and predicting evolutionary responses to environmental change is a fundamental goal shared between evolutionary and conservation biology (Flanagan, Forester, Latch, Aitken, & Hoban, 2018). Nancy Chen (University of Rochester) presented a keynote address on her work understanding the factors shaping temporal allele frequency changes in the federally threatened Florida Scrub Jay (Aphelocoma coerulescens), which have experienced significant population declines over the last century due to habitat destruction and fragmentation (Chen, Cosgrove, Bowman, Fitzpatrick, & Clark, 2016).…”
Section: Con S Ervati On Impli C Ati On S Of G Enome-to -Phenome-tomentioning
confidence: 99%
“…Such assessments can also help to identify the precise mechanism of diversity loss (e.g., correlated with habitat fragmentation; Jump, Hunt, & Peñuelas, ; Vranckx, Jacquemyn, Muys, & Honnay, ) and which human activities most impact the genetic variation and evolutionary potential of the species (Aguilar, Quesada, Ashworth, Herrerias‐Diego, & Lobo, ; DiBattista, ; Hoban et al., ). By monitoring genetic diversity through time, we can determine long‐term impacts and assess whether interventions have met conservation targets and improved biodiversity (this issue, Flanagan, Forester, Latch, Aitken, & Hoban, ; Hoban et al., ).…”
Section: Introductionmentioning
confidence: 99%